Impact of Implementation Regulation of the Minister of Marine and Fisheries Number 56 and 57 of 2014 to the Fishing Industry in Bitung, North Sulawesi - Stanny S Rawung; Ficke H Rawung (AIBPM Publisher, 2018)
The fishing industry is the dominant driver of the economy in Bitung, it brings Bitung City known by the term